2004
DOI: 10.1007/s00421-004-1098-1
|View full text |Cite
|
Sign up to set email alerts
|

Changes in von Willebrand factor and fibrinolysis following a post-exercise cool-down

Abstract: The purpose of this study was to determine the effect of a post-exercise active cool-down on von Willebrand factor and fibrinolysis. Ten subjects performed two maximal oxygen uptake (VO2max) tests followed by a 10-min passive (PC) or an active (AC) cool-down. Blood samples were obtained pre-exercise, post-exercise, post-PC/AC, and 1 h post-exercise and analyzed for von Willebrand factor antigen (vWf:Ag), tissue plasminogen activator (tPA) antigen and activity and plasminogen activator inhibitor-1 (PAI-1) activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 32 publications
(38 reference statements)
1
12
0
Order By: Relevance
“…However, regarding PTT, PT and vWF-Ag, our results reveled an increase in the mean values of PTT and PT because of weight loss and these findings agreed with Piccone et al (23) and Stratton et al concluded that a six months of endurance exercises resulted in reduction in fibrinogen and PAI-1 activity and enhanced the t-PA activity in elderly men (24). However, there was a significant reduction of vWF and these results are in line with Saenko et al (25) and Paton et al stated that serum vWf:Ag and tPA antigen were reduced in ten subjects performed two maximal oxygen uptake (VO2max) test trials (26).…”
Section: Discussionsupporting
confidence: 78%
“…However, regarding PTT, PT and vWF-Ag, our results reveled an increase in the mean values of PTT and PT because of weight loss and these findings agreed with Piccone et al (23) and Stratton et al concluded that a six months of endurance exercises resulted in reduction in fibrinogen and PAI-1 activity and enhanced the t-PA activity in elderly men (24). However, there was a significant reduction of vWF and these results are in line with Saenko et al (25) and Paton et al stated that serum vWf:Ag and tPA antigen were reduced in ten subjects performed two maximal oxygen uptake (VO2max) test trials (26).…”
Section: Discussionsupporting
confidence: 78%
“…First, the mode of exercise utilizes a small muscle group (forearm muscles), and therefore, we were unable to observe large changes in plasma vWF as compared to studies using whole-body exercise (Claus et al 2006; Paton et al 2004; Van den Burg et al 1995; Van den Burg et al 2000). Second, the majority of older individuals in this study had a medical history of cardiovascular disease that may have influenced the relationship between shear stress and endothelial function.…”
Section: Discussionmentioning
confidence: 90%
“…Unstable plaques rupture, resulting in thrombus formation that can completely occlude coronary arteries. Thus, plasma markers of coagulation potential and clot lysis (fibrinolysis) are clinically important [50,59]. Markers of coagulation potential include factors that make up the coagulation cascade and fibrinogen, the inactive precursor to fibrin.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we observed an increase in plasma Factor VIII following caffeine ingestion. The process of blood clot formation, or thrombosis, is preceded by several endothelial and luminary processes which can be enhanced by the increased presence of plasma clotting factors [1,38,46,50,59]. Factor VIII is a part of the intrinsic pathway of the coagulation cascade, the main pathway activated during exercise-induced stimulation of coagulation, and prior studies have consistently observed increases in this marker in response to exercise [50].…”
Section: Discussionmentioning
confidence: 99%